Complement as a therapeutic target - Harris, Claire (Henry Stewart Talks, 2017)
Physiological roles of complement, Complement activation and control, Complement-mediated disease, The challenges of complement drug discovery, Current drugs in the clinic, highlights and drawbacks, Strategies for complement inhibition, The current anti-complement drug development landscape